2020
DOI: 10.31557/apjcp.2020.21.7.2155
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Cisplatin-Induced Ototoxicity in Rats by L-arginine: The Role of Nitric Oxide, Transforming Growth Factor Beta 1 and Nrf2/HO-1 Pathway

Abstract: Background: Cisplatin is an alkylating agent that inhibits DNA replication and interferes with proliferation of cancer cells. However, the major limiting factor for its use is the possible development of adverse effects, including ototoxicity. Up till now, the mechanisms of this ototoxicity remain poorly understood. However, induction of oxidative stress and activation of the inflammatory cascade were suggested as contributing factors. Purpose: The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Similar to the results of our study, in a study examining the effects of L-arginine against CDDP-induced ototoxicity, it was found that besides a decrease in TNF-α levels, an increase in antioxidant levels and an increase in Nrf2/HO-1 (25).…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the results of our study, in a study examining the effects of L-arginine against CDDP-induced ototoxicity, it was found that besides a decrease in TNF-α levels, an increase in antioxidant levels and an increase in Nrf2/HO-1 (25).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, arginine activates NRF2 and upregulates the expression of the phase II metabolizing and antioxidative enzymes, thereby protecting ovine intestinal epithelial cells from LPS-induced cell death and oxidative damage (Zhang et al 2019 ). It also attenuates cisplatin–induced ototoxicity via the activation of the NRF2/HO-1 pathway among others in rats (Estfanous et al 2020 ).…”
Section: Introductionmentioning
confidence: 90%